2016
DOI: 10.4103/0253-7184.192121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic infections in sexually transmitted diseases attendees diagnosed with bacterial vaginosis, vaginal candidiasis, and trichomoniasis

Abstract: Background:Sexually transmitted diseases (STD) are a major health problem affecting mostly young people in both developing and developed countries. STD in women causes both acute morbidity and complications such as infertility, ectopic pregnancy, low-birth weight, and prematurity.Aims:The aim of the study is to assess the prevalence of bacterial vaginosis, vaginal candidiasis, and trichomoniasis among asymptomatic females attending STD outpatient department in a tertiary care hospital in South India.Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, their study population included women with mixed vaginal infections (aerobic vaginitis, candidiasis, and trichomoniasis) and not BV alone. Another study in India reported about 48.4% of asymptomatic BV cases but it was conducted in non-pregnant women [27]. So overall there appears to be some differences in the ndings, in relevance to the symptomatic vs. asymptomatic criteria which is most likely related to the different study populations and characteristics.…”
Section: Discussionmentioning
confidence: 89%
“…However, their study population included women with mixed vaginal infections (aerobic vaginitis, candidiasis, and trichomoniasis) and not BV alone. Another study in India reported about 48.4% of asymptomatic BV cases but it was conducted in non-pregnant women [27]. So overall there appears to be some differences in the ndings, in relevance to the symptomatic vs. asymptomatic criteria which is most likely related to the different study populations and characteristics.…”
Section: Discussionmentioning
confidence: 89%
“…Hence, patients with suspected STIs during an FP visit should be asked if they have a new partner, multiple partners, recent contacts, or if they are involved in high-risk sexual practices. Moreover as Rajalakshmi et al [23], physicians should assess the symptomatology, including that in the genital area, and check for the presence of ulcers, vesicles,and pustules, in addition to genital, rectal, or eye discharge. Furthermore, the skin should be examined for the presence of rash or scaling, and the physical exam should include assessment for lymphadenopathy, hepatosplenomegaly, and joint pain.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the skin should be examined for the presence of rash or scaling, and the physical exam should include assessment for lymphadenopathy, hepatosplenomegaly, and joint pain. All patients should also undergo the required tests to exclude STIs, including HIV,hepatitis B, and possible co-infections [23].Women should undergo a pelvic examination and a pregnancy test. Also, reinforcement of human papilloma virus and hepatitis B vaccination where appropriate should be performed.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical manifestations of trichomoniasis are characterized by the presence of yellow discharge, abnormal vaginal odor, and vulvar itching with signs of macular colpitis ("strawberry cervix"), purulent vaginal discharge, and vaginal and vulvar erythema [5]. However, various studies have reported prevalence of asymptomatic trichomoniasis ranging between approximately 30 and 35% [6][7][8]. On the other hand, the infection with T. vaginalis can lead to complications such as adnexitis, pyosalpingitis, and endometritis [9].…”
Section: Introductionmentioning
confidence: 99%